LA IMPORTANCIA Y NECESIDAD DE LA REGULACION EN LAS CONTRATACIONES IGUALES O MENORES A 8 UIT’S EN EL MARCO DE LA LEY N° 30225 LEY DE CONTRATACIONES DEL ESTADO Y LA LUCHA CONTRA LA CORRUPCION - Cieza Perez, Luis Kevin (2017)
The thesis that is presented, seeks to demonstrate that it is necessary and important a regulation in contracting equal or less than 8UITs in the framework of the current State Procurement Law, which will help to fight the corruption that progresses daily in the entities of the State In this research the transectional or transverse correlational design has been used, since it is sought to establish the relationship of the variables under study, it is important to point out that the sample extracted was from the 12 offices of Logistics and Supply of the Provincial Municipalities of the La Libertad Region, directed to those in charge of the Logistics or Supplying Offices according to the internal Chart of each Institution, 12 of whom were surveyed, using closed-ended questions. Thanks to this, it was demonstrated that contracting of 8 UITs or less must be regulated in a timely manner, and in this way to be able to make a more efficient and quality public expenditure, which can obtain public value for the citizens, since to execute its application it will be possible to reduce corruption in a good number, and to convert this fight as a State policy for the country's development, and this is based on a percentage of more than 70% of respondents who believe that regulation in this type of recruitment will benefit the work in the offices of logistics and supply transparent procedures and opening the market to new companies. KEY WORDS: Government Contracts, Public Management, Results Management, State Procurement, Fight against Corruption, State, Administrative Syste